Some remarks derived from the preparatory stages of the 1974 Athens Convention and its 2002 protocol - Işıklar, Güneş Karol (Polish Review of International and European Law, 2020)
The preparatory stages of the 2002 Athens Convention are helpful in finding answers to some of the questions of interpretation. Within this context, the observations and the decisions of the IMO Legal Committee, as well as the proposals and observations submitted by the delegations participating its sessions during the preparation of the draft text of the 2002 Protocol, might guide one to draw a conclusion. Among these questions exist the manner of application of the provision regarding the liability of the carrier in terms of the contributory fault or neglect of the passenger, or his or hers mental injury, or the possibility of maintenance of personal accident insurance. Additionally, the 1974 Athens Conference might also be regarded as helpful in order to interpret the rules relating to the performing carrier and the situation of the gratuitous carriage in terms of the Convention.